Differential Gene Expression in Liver Tissues of Streptozotocin-Induced Diabetic Rats in Response to Resveratrol Treatment - Sadi, Gokhan; Baloglu, Mehmet Cengiz; Pektas, Mehmet Bilgehan (Public Library of Science (PLoS), 2015)
This study was conducted to elucidate the genome-wide gene expression profile in streptozotocin induced diabetic rat liver tissues in response to resveratrol treatment and to establish differentially expressed transcription regulation networks with microarray technology. In addition to measure the expression levels of several antioxidant and detoxification genes, real-time quantitative polymerase chain reaction (qRT-PCR) was also used to verify the microarray results. Moreover, gene and protein expressions as well as enzymatic activities of main antioxidant enzymes; superoxide dismutase (SOD-1 and SOD-2) and glutathione S-transferase (GST-Mu) were analyzed. Diabetes altered 273 genes significantly and 90 of which were categorized functionally which suggested that genes in cellular catalytic activities, oxidation-reduction reactions, co-enzyme binding and terpenoid biosynthesis were dominated by up-regulated expression in diabetes. Whereas; genes responsible from cellular carbohydrate metabolism, regulation of transcription, cell signal transduction, calcium independent cell-to-cell adhesion and lipid catabolism were down-regulated. Resveratrol increased the expression of 186 and decreased the expression of 494 genes in control groups. While cellular and extracellular components, positive regulation of biological processes, biological response to stress and biotic stimulants, and immune response genes were up-regulated, genes responsible from proteins present in nucleus and nucleolus were mainly down-regulated. The enzyme assays showed a significant decrease in diabetic SOD-1 and GST-Mu activities. The qRT-PCR and Western-blot results demonstrated that decrease in activity is regulated at gene expression level as both mRNA and protein expressions were also suppressed. Resveratrol treatment normalized the GST activities towards the control values reflecting a post-translational effect. As a conclusion, global gene expression in the liver tissues is affected by streptozotocin induced diabetes in several specific pathways. The present data suggest the presence of several processes which contribute and possibly interact to impair liver functions in type 1 diabetes, several of which are potentially amenable to therapeutic interventions with resveratrol.
Keywords: Male; Science; Gene Expression Profiling; Q; Body Weight; R; Streptozocin; Diabetes Mellitus, Experimental; Rats; Oxidative Stress; Liver; Resveratrol; Hyperglycemia; Stilbenes; Medicine; Animals; Rats, Wistar; Research Article; 2. Zero hunger; 3. Good health